Surveying community needs regarding the use of agricultural technology innovations and marketing techniques to improve farmers' income - ตะพาบน้ำ, กรยุทธ; เชียงคำ, สมบัติ; พิทักษ์วงศ์, บัณฑูร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purpose of this study is to explore the needs of farmers in agricultural innovation and technology transfer, including the marketing skills of farmers in the experimental area. The target group is specific groups, namely farmers in five counties in the middle of Ma 'an County, Chiang Mai Province. Only the farmers group, that is, the area at the foot of the mountain, is selected because it is a group with room for action. The sample group consisted of 33 male and female farmers of all ages, and a five-level questionnaire survey is conducted by using research tools. The statistical data used in analyzing the data include the average value and standard deviation, and Cronback is used,            Results of the study of community needs when using a test that included operational activities to survey the needs of farmers participating in the Agricultural Partnership Project for marketing promotion. In subtopics 1)-5), the results of the study of community needs It was found that the demand for the use of advertising and public relations was at the "high" level (average 3.61), the demand for marketing management was at the "high" level (x̄= 3.55), the demand for the use of marketing networks was at the "high" level. “Very high” (x̄= 3.63). The need for innovation in adding product value is at the “high” level (x̄= 3.60). The readiness in terms of potential of project partners is at the “high” level (x̄= 3.57).